Model Pengelolaan Fasilitas Masjid Untuk Para Musafir Studi Kasus Masjid Raya Al-Falah Sragen - Hakim, Lukmanul; Susanto, Dedy; Nurbini; Fitria, Ani (Journal of Islamic Management, 2026)
Mosques have an important role in meeting the needs of travelers, especially in the midst of increasing community mobility. Masjid Raya Al-Falah Sragen is a strategic example as a traveler-friendly religious stopover. This study aims to examine the role of the mosque in serving travelers and its facility management model. The method used is descriptive qualitative through interviews, observations, and documentation studies. The results showed that Masjid Raya Al-Falah Sragen, under the management of Ust. Kunadi Ikhwani, provides professional services with a SMART goals-based approach. Management is carried out through digitalization, the formation of the Mosque Executive Board (BEM), and youth regeneration. Available facilities include luggage storage, rest rooms, clean toilets, and cashless technology. This mosque management model emphasizes comfort, safety, and inclusiveness with the IHSAN principle. The mosque not only functions as a place of worship, but also as a community center that supports social and religious development.